Kampanye Media Berperspektif Gender dalam Upaya Pencegahan Kekerasan Seksual pada Instagram Satgas PPKS - Riska Widiyanti; Tri Wuryaningsih; Soetji Lestari (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2023)
The research aims to reveal the form of a media campaign from a gender perspective. The campaign was carried out by the Task Force for Preventing and Handling Sexual Violence at Jakarta State University and Jenderal Soedirman University. The research employs Antonio Gramsci's Hegemony Theory as a tool of analysis. Furthera more, qualitative approach was used to understand the form of media campaigns by gender perspective carried out by the Task Force for Preventing and Handling Sexual Violence at Jakarta State University and Jenderal Soedirman University. The type of research was netnography. The data was collected by documentation. The results of the study showed there were two categories of media campaigns by gender perspective during the 2022 - 2023 period done by those two Instagram accounts. It was education about gender equality and how to prevent and handle sexual violence for campus residents. It was found that the form of media campaign carried out still did not meet the requirements. The content should involve the prevention efforts in CHAPTER IV Article 34 point (d) Permendikbudristek Number 30 of 2021. It was mentioned that the PPKS Task Force is also tasked with providing education related to disability equality sexual and reproductive health education. A gender perspective should be involved in every campaign of the PPKS Task Force. It is essential to encourage discourse hegemony in the form of media campaigns able to strengthen the efforts to prevent sexual violence in university